Stereoselective effects of lysophosphatidylserine in rodents. - Chang, H. W. (1988)
1. The pharmacological action of the L- and D-enantiomers of lysophosphatidylserine has been studied in vivo by following the increase in blood and brain glucose content caused by this phospholipid in mice. Preliminary experiments have confirmed that these effects are the consequence of lysophosphatidylserine-induced mast cell activation since they are not observed in mast cell-deficient mice bearing the W/Wv genotype. 2. Maximal hyperglycaemic response and brain glucose accumulation occur at 10 mg kg-1 lysophosphatidyl-L-serine (i.v.). Half-maximal effect is at 3.5 mg kg-1. Lysophosphatidyl-D-serine at doses of up to 25 mg kg-1 i.v. elicits 40% (blood glucose) and 60% (brain glucose) of the maximal effect. The difference in activity between the two enantiomers is also observed in the desensitization to lysophosphatidylserine occurring when this phospholipid is administered by the oral route. 3. Lysophosphatidyl-L-serine is more active than the D-enantiomer in mouse isolated peritoneal mast cells. Activity ratios of 10 are observed between 20 and 50% histamine release. Similar results are obtained with rat isolated peritoneal mast cells. 4. It is concluded that the configuration of the alpha carbon atom of serine influences the activity of lysophosphatidylserine in vivo and in vitro. Thus, the appropriate position of the serine amino group is required for optimal interaction of the phospholipid head group and a receptor in the mast cell membrane.